Calcium Sensors STIM1 and STIM2 Regulate Different Calcium Functions in Cultured Hippocampal Neurons - Kushnireva, Liliya; Korkotian, Eduard; Segal, Menahem (Frontiers in Synaptic Neuroscience, 2021)
There are growing indications for the involvement of calcium stores in plastic properties of neurons and particularly in dendritic spines of central neurons. The store-operated calcium entry (SOCE) channels are assumed to be activated by the calcium sensor STIM which lead to activation of its associated Orai channel. There are two STIM species, and the differential role of the two in SOCE is not entirely clear. In the present study we were able to distinguish between transfected STIM1, which is more mobile primarily in young neurons, and STIM2 which is less mobile and more prominent in older neurons in culture. STIM1 mobility is associated with spontaneous calcium sparks, local transient rise in cytosolic [Ca2+]i, and in formation and elongation of dendritic filopodia/spines. In contrast, STIM2 is associated with older neurons, where it is mobile and moves into dendritic spines primarily when cytosolic [Ca2+]i levels are reduced, apparently so as to activate resident Orai channels. These results highlight a role for STIM1 in the regulation of [Ca2+]i fluctuations associated with the formation of dendritic spines or filopodia in the developing neuron, whereas STIM2 is associated with maintenance of calcium entry into stores in the adult neuron.